Posterior Resin Bonded Fixed Dental Prosthesis - A Case Report (Bangladesh Journal of Dental Research & Education, 2015)
Dentistry is an ever evolving science. With the advancements in the field of bonding techniques and also in the tooth preparation methods, the use of Resin bonded fixed dental prostheses is becoming a treatment of choice for small posterior edentulous spans. DOI: http://dx.doi.org/10.3329/bjdre.v5i1.22458 Bangladesh Journal of Dental Research and Education Vol.5(1) 2015: 26-28